Cracking Machine / Muhammad Imtihan Ismail - Ismail, Muhammad Imtihan (2020)
The business that we created is based on our innovation and the product is Kuaci Cracker Machine. This product give benefit to people who used when eating the sunflower seed. The benefit of the product is can save the time for open the sunflower seed. The machine also come with led light so that the user can see the machine even in the dark. The machine also come with protection so the user will not be being injured when operating the machine. The machine can be used at anywhere because it come with battery so that the user can charged and used it when needed. Kuaci Cracker Machine is unique because the design that we created will make the user like to use it. The Kuaci Craker machine also light and durable that make the toughness of the machine is high. The machine also can be user friendly because we provided simple instruction to operate the machine. The user can be man or woman because it is no complicated to use the product. The people who want these product need to order through official website or they can get the product direct from our company. Our business will become more developed in the future so that we can attract more people to buy our product.